ANALISIS PENGELOLAAN ASET TETAP DAERAH PADA DINAS PENGELOLAAN KEUANGAN ASET DAERAH (DPKAD) PROVINSI ACEH - Labasido, Esduo Ramadhano; Darwanis, Darwanis (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2019)
Fixed assets is one of the elements that must be managed properly in order to produce reliable information in the financial statements region. Orderly management of regional property (fixed assets) carries a significant effect on the perfection of regional balance sheet presentation. The purpose of this study to determine the suitability of fixed asset management at the Department of Finance and Asset Management Revenue Region (DPKAD) Aceh with Regulation of the Minister of the Interior 19 of 2016 visits from local property management cycle is applied as well as the completeness of the document source. The method used is a qualitative with descriptive analysis techniques. The results showed that DPPKAD Aceh as maid manager has implemented 10 cycles in the management of fixed assets. From 14 document source needed only 13 documents are there, so that the management of fixed assets in DPPKAD Aceh with Regulation 19 of 2016 has not been fully fit. Preferably, DPPKAD Aceh perform better coordination with all SKPDs as users/ parties responsible in making List of Regional Property Maintenance Requirements (DKPBMD) and List of Results Maintenance Goods as a form of compliance with applicable regulations.